2007
DOI: 10.1093/aob/mcm129
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Analysis Based on Nucleotide Sequence of a Marker Linked to the Brittle Rachis Locus Indicates a Diphyletic Origin of Barley

Abstract: Background and AimsBarley (Hordeum vulgare ssp. vulgare) cultivation started between 9500 and 8400 years ago, and was a major part of ancient agriculture in the Near East. The brittle rachis is a critical trait in the domestication process.MethodsA DNA sequence closely linked to the brittle rachis complex was amplified and resequenced in a collection of cultivated barleys, wild barleys (H. vulgare ssp. spontaneum) and weedy brittle rachis varieties (H. vulgare ssp. vulgare var. agriocrithon). The sequence was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 23 publications
6
53
0
Order By: Relevance
“…Extensive work has been devoted to establishing monophyly versus polyphyly with mixed results. Some gene phylogenies showed evidence of monophyly, such as in the case of flax (Allaby et al, 2005), while others indicated polyphyly as in the case of rice and barley (Londo et al, 2006, MolinaCano et al, 2005, Azguvel and Komatsuda 2007. However, the multiregionalism suggested by polyphyly still assumes a rapid process in which gene flow between nascent crop populations does not occur.…”
Section: Genetic Analysis Within the Rapid Transition Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work has been devoted to establishing monophyly versus polyphyly with mixed results. Some gene phylogenies showed evidence of monophyly, such as in the case of flax (Allaby et al, 2005), while others indicated polyphyly as in the case of rice and barley (Londo et al, 2006, MolinaCano et al, 2005, Azguvel and Komatsuda 2007. However, the multiregionalism suggested by polyphyly still assumes a rapid process in which gene flow between nascent crop populations does not occur.…”
Section: Genetic Analysis Within the Rapid Transition Paradigmmentioning
confidence: 99%
“…In the case of the tough rachis mutation, most crops have a single underlying mutation responsible for the trait, with the notable exception of barley that has two (Takahashi 1972, Azguvel andKomatsuda 2007), seemingly supporting the rapid transition paradigm. However, the genetic expectation becomes quite different under the protracted transition paradigm, Fig.…”
Section: The Chronology Of Trait Fixationmentioning
confidence: 99%
“…It is assumed that such mutations occur within cultivated crops because they would be rapidly removed through purifying selection from wild populations, and so independent domestications would select independent mutations. In many crops only one tough rachis mutant is known, supporting a single origin on this evidence, although barley is an unusual case in that two mutants are known (12,13). The second line of inquiry has considered the reduction in genetic diversity associated with the domestication bottleneck.…”
mentioning
confidence: 95%
“…Many reports indicate that cultivated barley was first domesticated about 10,000 y ago in the Near East Fertile Crescent (3,5). However, the debate on the monophyletic or polyphyletic origin of barley still remains contentious (1,(5)(6)(7)(8)(9). Morrell and Clegg, based on the resequencing data from 18 loci, proposed that barley has been domesticated at least twice, once in the Near East Fertile Crescent and then 1,500-3,000 km farther east (7).…”
mentioning
confidence: 99%